LIQUID CHROMATOGRAPHIC ANALYSIS OF CAROTENOIDS IN FOODS - Dincel, Demet; Kepekci Tekkeli, Serife Evrim; Önal, Cem; Önal, Armağan; Sagirli, Olcay (Journal of the Chilean Chemical Society, 2019)
Current scientific studies indicate that carotenoids (CRTDs) are beneficial for maintaining health and lowering the risk of different pathologies. Considering the increasing role of carotenoids in healthcare, determination of carotenoid content of foods become important. Mostly, the analytical procedures that are used for this aim, are based on extraction techniques followed by different analytical procedures, especially high performance liquid chromatography. In this publication, a review of various analytical techniques developed for the determination of carotenoids in different food commodities starting from 2006 up to now, has been presented. Abbrevations: CRT, Carotene; CRTD, Carotenoid; AA, Ascorbic acid; LT, Lutein; CRX, Cryptoxanthin; ZX, Zeaxanthin; HPLC; High Performance Liquid Chromatography; DAD, Diode Array Detector; PDA, Photodiode Array; UV, Ultraviyolet spectroscopy; LC-MS, Liquid Chromatograhy-Mass Spectroscopy; APCIMS, Atmospheric Pressure Chemical Ionization Mass Spectrometry; DIDA, Diastereomeric Dilution Assay; HF-LPME, Hollow Fiber Liquid-phase Microextraction; UPLC, Ultra Performance Liquid Chromatography; GC-MS, Gas Chomatography-Mass Spectroscopy; ELSD, Evaporative Light Scattering Detection; TQMS, Triple-Quadrupole Mass Spectroscopy.